A GREAT REPRESENTATIVE OF TURKISH SUFISM (Scientific journal of the Fergana State University, 2025)
This article provides information about Suleyman Bokirgani, a talented disciple of the founder of the world-famous Yasaviya order, Khoja Ahmed Yasavi, a unique representative of the Turkish Sufi Sharia. The socio-philosophical analysis of the spiritual heritage of Suleyman Bokirgani is important for the education of young people. The article reflects that his teachings on the education of the human spirit are an important school of thought that should be studied by future generations.